2013
DOI: 10.1124/jpet.113.207704
|View full text |Cite
|
Sign up to set email alerts
|

Spinal-Supraspinal and Intrinsicµ-Opioid Receptor Agonist-Norepinephrine Reuptake Inhibitor (MOR-NRI) Synergy of Tapentadol in Diabetic Heat Hyperalgesia in Mice

Abstract: Tapentadol is a m-opioid receptor (MOR) agonist and norepinephrine reuptake inhibitor (NRI) with established efficacy in neuropathic pain in patients and intrinsic synergistic interaction of both mechanisms as demonstrated in rodents. In diabetic mice, we analyzed the central antihyperalgesic activity, the occurrence of site-site interaction, as well as the spinal contribution of opioid and noradrenergic mechanisms in a hotplate test. Tapentadol (0.1-3.16 mg/animal) showed full efficacy after intrathecal as we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 36 publications
0
16
0
Order By: Relevance
“…In line with this idea, new molecules that integrate additional mechanisms to the opioid receptor agonism have been shown efficacy in reducing nociceptive behavior in animal models of DNP, such as the cebranopadol, a nociceptin/orphanin FQ peptide and opioid receptor agonist [166] , and the mu opioid receptor agonist and norepinephrine reuptake inhibitor, tapentadol [162,167] . The latter was approved by FDA for DNP treatment since 2012 [11] .…”
Section: Opioidsmentioning
confidence: 97%
“…In line with this idea, new molecules that integrate additional mechanisms to the opioid receptor agonism have been shown efficacy in reducing nociceptive behavior in animal models of DNP, such as the cebranopadol, a nociceptin/orphanin FQ peptide and opioid receptor agonist [166] , and the mu opioid receptor agonist and norepinephrine reuptake inhibitor, tapentadol [162,167] . The latter was approved by FDA for DNP treatment since 2012 [11] .…”
Section: Opioidsmentioning
confidence: 97%
“…Tapentadol ER was administered to 588 patients for a 3-week open-label phase, and subsequently, 395 patients with at least a one-point reduction in pain intensity were randomized 1:1 to receive placebo or the optimal fixed dose of tapentadol ER for a 12-week double-blind phase to show a highly significant reduction in pain intensity for those on active treatment [Schwartz et al 2011]. The mechanism of action is thought to be via opioid spinal-supraspinal synergy, as well as intrinsic spinally mediated μ-opioid receptor agonist-norepinephrine reuptake inhibitor effect [Christoph et al 2013]. The other opioid that has been studied in PDN is oxycodone, which has higher bioavailability and potency compared with morphine and a reduced side-effect profile.…”
Section: Symptomatic Treatmentmentioning
confidence: 99%
“…Patients in the tapentadol arm of this trial reported a significant reduction in pain intensity compared with placebo. It has been proposed that tapentadol suppresses neuropathic pain through opioid spinal-supraspinal synergy in addition to the µ-opioid agonist and norepinephrine inhibitory effect [124].…”
Section: Opioid Analgesiamentioning
confidence: 99%